Reduced-scale study of the coupling between thermal and wind effects on the ventilation systems of nuclear facilities. Issue 1 (2nd January 2021) - Le Dez, Thomas; Richard, Jérôme; Inard, Christian; Le Roux, Nicolas; Demouge, François; Faure, Xavier; Ricciardi, Laurent
Abstract: To study heat and mass transfers inside nuclear facilities equipped with ventilation systems, a methodology was developed to carry out reduced-scale experiments for studying flows induced by thermal and wind effects simultaneously. The methodology was numerically validated on simple configurations and applied to a reference configuration representative of nuclear facilities. The effects of wind and thermal phenomena on heat and mass transfers in various ventilation situations (normal ventilation or ventilation switched off) and scenarios of heat supply were studied in wind tunnel experiments. The thermal sources that could be generated by an industrial process were reproduced experimentally with a helium injection. The objectives of this article are to present the scaling-down methodology and the main experimental results concerning the influence of thermal effects on airflows in the reduced-scale model. The effects of heat with or without wind on loss of building containment were also highlighted and analysed. Finally, the reliability of SYLVIA simulation software, which was used to support safety assessments in nuclear facilities, was analysed using the experimental results.